Analysis of the Use of Learning Media Applications in Online Geography Subjects During the Covid-19 Pandemic for Senior High School Students - MS Khabibur Rahman; Bayu Kurniaaji; Agus Sudargono; Pranichayudha Rohsulina (Jurnal Komunikasi Pendidikan, 2022)
Learning media applications are learning concepts that are carried out through electronic media networks in the form of mobile and non-mobile applications. The development of very advanced technology in the modern era and globalization allows various activities to be carried out quickly and efficiently. Technological developments have had a lot of influence on our way of life, one of which is in the field of education by using online or online learning media applications in learning activities in schools, colleges, courses and even online communities have started using concepts like this. The purpose of this study was to find out how the role of learning media applications in geography subjects in education was during the covid-19 pandemic. As we all know, the losses due to the COVID-19 virus have had a huge impact on all sectors, including the education sector. To achieve this goal, this research will use a qualitative research approach. This research is a type of qualitative descriptive research. Analysis of the data used in processing questionnaire data through google form by describing the results of the questionnaires distributed online.